2019
DOI: 10.1371/journal.pone.0210624
|View full text |Cite
|
Sign up to set email alerts
|

District-level health management and health system performance

Abstract: Strengthening district-level management may be an important lever for improving key public health outcomes in low-income settings; however, previous studies have not established the statistical associations between better management and primary healthcare system performance in such settings. To explore this gap, we conducted a cross-sectional study of 36 rural districts and 226 health centers in Ethiopia, a country which has made ambitious investment in expanding access to primary care over the last decade. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 19 publications
(24 reference statements)
7
53
4
1
Order By: Relevance
“…The improvements may be related to the practice of effective management which has direct implications in in uencing availability input and redesigning of processes (14). A study in Ethiopia also showed that improving competencies at the district level can improve service availability and quality by improving capacity of management at the facility level, coordination, resource availability and accountability (4).…”
Section: Discussionmentioning
confidence: 99%
“…The improvements may be related to the practice of effective management which has direct implications in in uencing availability input and redesigning of processes (14). A study in Ethiopia also showed that improving competencies at the district level can improve service availability and quality by improving capacity of management at the facility level, coordination, resource availability and accountability (4).…”
Section: Discussionmentioning
confidence: 99%
“…state, regional, district, sub-district), is frequently perceived as a way to improve health system performance as local authorities are better able to make informed decisions regarding local conditions [1][2][3]. However, in order to improve performance, individual capacity among local health managers are needed [1,[4][5][6]. Moreover institutional capacities, such as functional support systems and enabling work environments, including an appropriate level of autonomy for the managers', must be in place [7].…”
Section: Introductionmentioning
confidence: 99%
“…planning, supervising, monitoring quality and coverage), resources (i.e. staff, budgets, drugs, equipment, buildings and information), and stakeholders (external relations, partners, community members, service users and intersectoral stakeholders) [4,16,17]. Literature suggests weak management and leadership capacities among local health managers globally [7,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The workforce who are competent to lead, manage and govern improve the health system performance and health outcomes. (1)(2)(3)(4)(5) Because, it supports them to balance people's needs, workloads and organizations' requirements simultaneously. (6) Thus, a continuous deal in this area is important due to knowledge development and technological innovations.…”
Section: Introductionmentioning
confidence: 99%